2019
DOI: 10.1186/s13148-019-0775-1
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II intra-patient dose escalation study of vorinostat in children with relapsed solid tumor, lymphoma, or leukemia

Abstract: BackgroundUntil today, adult and pediatric clinical trials investigating single-agent or combinatorial HDAC inhibitors including vorinostat in solid tumors have largely failed to demonstrate efficacy. These results may in part be explained by data from preclinical models showing significant activity only at higher concentrations compared to those achieved with current dosing regimens. In the current pediatric trial, we applied an intra-patient dose escalation design.The purpose of this trial was to determine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…Additionally, histone deacetylase (HDAC) inhibitors have been shown to impede MYC -amplified Group 3 medulloblastoma tumor growth in vitro [ 14 , 15 , 39 , 44 ]. Due to the focal MYC amplification, our patient received single-agent vorinostat, an oral HDAC inhibitor that is well tolerated in children with relapsed CNS tumors [ 19 , 24 , 31 , 50 ], following his first relapse. However, he presented with progressive disease after seven months.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, histone deacetylase (HDAC) inhibitors have been shown to impede MYC -amplified Group 3 medulloblastoma tumor growth in vitro [ 14 , 15 , 39 , 44 ]. Due to the focal MYC amplification, our patient received single-agent vorinostat, an oral HDAC inhibitor that is well tolerated in children with relapsed CNS tumors [ 19 , 24 , 31 , 50 ], following his first relapse. However, he presented with progressive disease after seven months.…”
Section: Discussionmentioning
confidence: 99%
“…Many anti-tumor drugs approved for use in adults and children are currently under evaluation for their potential to act as LRAs in adults with HIV ( Table 3 ). Existing anti-tumor drugs are easily translatable to LRA discovery because of the shared strategy to induce epigenetic changes that promote cell cycle arrest, apoptosis, autophagy, and cell death of cancer-infected cells ( 163 ). Several LRAs have undergone testing in adult clinical trials including the histone deacetylase inhibitors, such as vorinostat, panobinostat, belinostat, and romidepsin, as well as immunomodulatory compound such as IL-15 receptor superagonist complex (N-803).…”
Section: Passive Immunization Strategiesmentioning
confidence: 99%
“…A recent study demonstrated that HDAC inhibitors stabilize the MYC protein and thus lead to reduced DNA binding and ultimately lower expression of MYC target genes [63]. Furthermore, a combined phase I/II dose escalation trial showed overall manageable toxicity and partial responses in a fraction of patients (including eight MB patients) for the HDAC inhibitor Vorinostat [68]. This is in line with another study that showed a good safety profile for the combination of Vorinostat and Temozolomide in a small cohort of children with relapsed CNS malignancies, including two MB patients (NCT01076530) [69].…”
Section: Hdac Inhibitorsmentioning
confidence: 99%